Evaluation of strategies for identification of infants with pathogenic glucose-6-phosphate dehydrogenase variants in China - Xia, Zhongmin; Wang, Xudong; Ye, Huiming; Gao, Chunliu; Zhou, Xiaoman; Chen, Jing; Ge, Yunsheng; Li, Juan; Zhou, Yulin; Guo, Qiwei (Frontiers in Genetics, 2022)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency, which is caused by pathogenic variants of G6PD that result in decreased G6PD activity, is an X-linked inherited inborn error of metabolism that occurs worldwide. Individuals with G6PD deficiency and heterozygous females with normal G6PD activity (i.e. all individuals with pathogenic G6PD variants) are at risk of developing hemolytic anemia under increased oxidative challenge. However, this risk can be minimized by timely diagnosis. Currently, two assays are used to diagnose G6PD deficiency in China: evaluation of enzymatic activity and targeted genotyping. In terms of identification of all individuals with pathogenic G6PD variants, the performance and cost of different diagnostic strategies (isolated or combined evaluation of G6PD activity and G6PD genotyping) can vary, and these factors should be comprehensively evaluated. In this study, we examined 555 infants (437 males and 118 females) who were positive for the newborn screening of G6PD deficiency. We first evaluated the diagnostic performances of enzymatic testing and targeted genotyping. Both assays attained 100% specificities and positive predictive values for both male and female infants. In contrast, the sensitivities and negative predictive values (NPVs) of the diagnostic tests were different for male and female infants. For male infants, the sensitivities were 99.8% and 98.3%, and the NPVs were 94.1% and 69.6%, for enzymatic testing and targeted genotyping, respectively. For female infants, the sensitivities were 62.5% and 97.9%, and the NPVs were 37.9% and 91.7%, for enzymatic testing and targeted genotyping, respectively. We also evaluated the cost of the five different diagnostic strategies. The combination of G6PD activity testing of all infants, followed by genotyping of female infants with normal G6PD activity, attained high diagnostic sensitivity (99.8%) at a low cost (8.60 USD per diagnosed case). In the future, simultaneous examination of G6PD activity and whole-exon or whole-gene G6PD sequencing could become a standard clinical practice. Our data provide references for clinical practice on the standardization of current and future interventions for G6PD deficiency in China.